PJMHS 2022
DOI: 10.53350/pjmhs22167461
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Medical College Lib Guides: A Usability Case Study

Abstract: Many libraries have adopted usability testing as a standard practise for ensuring that their online presence is user-friendly and accessible. This study attempt to test usability of LibGuides platform at Shalamar Teaching Hospital, Lahore. The purpose of this qualitative research is to examine the usability, user experience (UX), and information architecture (IA) of LibGuides in the institutional context of Shalamar Medical & Dental College, Lahore, The research explored users’ views and was then e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(51 citation statements)
references
References 7 publications
(8 reference statements)
0
5
0
Order By: Relevance
“…They concluded that when anger is suppressed, it leads to the underlying cause of anxiety and depression. Therefore, medical students who will have to deal with every kind of patient are needed to know and practice 16,17,18,19,20,21 how to manage anger. And the best way to manage and control anger is the one that Islam teaches us.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They concluded that when anger is suppressed, it leads to the underlying cause of anxiety and depression. Therefore, medical students who will have to deal with every kind of patient are needed to know and practice 16,17,18,19,20,21 how to manage anger. And the best way to manage and control anger is the one that Islam teaches us.…”
Section: Discussionmentioning
confidence: 99%
“…They will improve their education and collection of resources. 16,17,18,19,20,21 Therefore, by conducting this research we were aiming to focus on medical college students as their lifestyle is comparatively more stressful than ordinary college goers 6 . The aim of this study is to asses knowledge, attitude and practice of anger management among medical students and its effect on their daily life and position in the society.…”
Section: Introductionmentioning
confidence: 99%
“…Medical students and health professionals have e-resources and can get through their college or hospital libraries, they also preferred and seek knowledge for their education and research work. 13,14,15,16,17,18,19 These advances incorporate social networking destinations, wikis, podcasts and weblogs (blogs). Web 2.0 applications allow users to not as it were recover data but to utilize the network as a stage to form and claim the data.…”
Section: Introductionmentioning
confidence: 99%
“…Press releases, media files, newsletters, public relations and content are examples of these 7 . These resources provide material that has been adapted for student utilization, such as scientific and research data 8,9 .…”
Section: Introductionmentioning
confidence: 99%